PRODUCTION OF MIXED FRUIT WINES USING Saccharomyces cerevisiae ISOLATED FROM PALM WINE. - U.O. EDEGHOR; J.E. EGBELO; J.C. NWOKPURU; C.O ACHOKWU; V.C. IGWE (African Journal of Health, Safety and Environment, 2026)
Postharvest losses and rapid nutrient degradation due to fruit spoilage necessitate alternative preservation methods. Wine production presents a viable approach to minimizing fruit waste while retaining essential nutrients. In this study, mixed fruit wines were produced from watermelon, banana and pineapple using Saccharomyces cerevisiae isolated from fresh palm wine as a starter culture. After secondary fermentation, the wines maintained an acidic pH range (2.29±0.1 to 3.25±0.2), a stable fermentation temperature (26.50±1.1°C to 27.00±1.1°C), specific gravity values of 1.021±0.02 kg/L and 1.027±0.03 kg/L and total acidity levels of 1.57±0.2% and 2.11±0.1% for Wines A and B, respectively. The final alcohol content was 8.40±2.9% in Wine A and 9.84±3.6% in Wine B. Proximate analysis showed retention of key nutrients after clarification and maturation and sensory evaluation indicated greater consumer preference for Wine B (P>0.05). These findings demonstrate that locally sourced S. cerevisiae strains from palm wine can serve as an efficient starter culture for fruit wine fermentation and support the utilization of mixed fruits as a sustainable raw material for value-added wine production. This approach not only mitigates fruit wastage but also provides an economic avenue to enhance fruit utilization.